2007
DOI: 10.1093/toxsci/kfm083
|View full text |Cite
|
Sign up to set email alerts
|

Rodent Carcinogenicity Profile of the Antidiabetic Dual PPAR α and γ Agonist Muraglitazar

Abstract: The carcinogenic potential of muraglitazar, a dual human peroxisome proliferator-activated receptor alpha/gamma agonist, was evaluated in 2-year studies in mice (1, 5, 20, and 40 mg/kg) and rats (1, 5, 30, and 50 mg/kg). Benign gallbladder adenomas occurred at low incidences in male mice at 20 and 40 mg/kg (area under the curve [AUC] exposures > or = 62 times human exposure at 5 mg/day) and were considered drug related due to an increased incidence of gallbladder mucosal hyperplasia at these doses. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 24 publications
2
34
0
2
Order By: Relevance
“…However, side effects of PPAR␣/␥ dual agonists still make them unsuitable for treatment of obesity and insulin resistance (Hellmold et al, 2007;Mittra et al, 2007;Tannehill-Gregg et al, 2007). In this regard, the failure of former PPAR␣/␥ dual agonists prompted us to develop novel PPAR␣/␥ dual agonists without (or with less) deleterious effects by screening different backbone structures of PPAR ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, side effects of PPAR␣/␥ dual agonists still make them unsuitable for treatment of obesity and insulin resistance (Hellmold et al, 2007;Mittra et al, 2007;Tannehill-Gregg et al, 2007). In this regard, the failure of former PPAR␣/␥ dual agonists prompted us to develop novel PPAR␣/␥ dual agonists without (or with less) deleterious effects by screening different backbone structures of PPAR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently identified PPAR␣/␥ dual agonists were ineffective because of undesirable side effects during preclinical or clinical trials. For example, muraglitazar, a synthetic PPAR␣/␥ dual agonist, was aborted during clinical trials because of increased mortality, fluid retention, edema, and cancer (Mittra et al, 2007;Tannehill-Gregg et al, 2007), and tesaglitazar was reported to cause fibrosarcoma in subcutaneous tissues (Hellmold et al, 2007). Furthermore, it has recently been reported that several types of TZDs induce tissue toxicity (Lloyd et al, 2002;Nissen and Wolski, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained urothelial proliferation may cause fixation of spontaneous mutation of mucosal cells, and finally develop tumors in urinary bladder and/or renal pelvis. Recently, a 2-year carcinogenicity study and a mechanistic study of Muragliazar, a PPAR dual agonist, provided some evidence for the proposed MOA 19,20 . Similar working hypotheses on M O A s a r e b e i n g p r o p os e d b y t he H e m a n g i o m a / Hemangiosarcoma and Fibrosarcoma/Liposarcoma Working Groups of the project, and further work toward elucidation of MOAs and evaluation of human risks is expected.…”
Section: Moa Of Carcinogenicity Of Ppar Agonists and The Ilsi-hesi Ppmentioning
confidence: 99%
“…These safety concerns include potential carcinogenicity, weight gain, fluid retention, and increased risk of cardiac failure (Mittra et al, 2007;Nissen et al, 2005;Tannehill-Gregg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%